الخطأ الطبي وأثره علي المريض: دراسة فقهية معاصرة - حسين، نواف حفظ الله غازي (جامعة الأندلس للعلوم والتقنية, 2021)
يهدف بحث الخطأ الطبي وأثره على المريض دراسة فقهية معاصرة؛ إلى بيان الحاجة الملحة للبيان الفقهي في هذا الجانب، وتبدو أهمية الموضوع واضحة كونه يتعلق بحياة الناس التي هي ضرورة من الضرورات. وقد تحددت إشكالية البحث في السؤال الآتي: هل يتحمل الطبيب والجراح والمخدر في وقتنا المعاصر الخطأ الطبي أم لا؟ واقتضى هذا البيان منهجية الوصف والتحليل والمقارنة والترجيح للمذاهب والآراء الفقهية عند الفقهاء، مما يجعل الشريعة باسطة ذراعها على الحياة من كل جوانبها. وتكون مسار البحث الهيكلي من ثلاثة مباحث تضمن المبحث أول: تعريف الخطأ الطبي وأنواعه. أما المبحث الثاني: فقد تضمن بيان المسؤولية الطبية والمرفق الصحي، ومقدار هذه المسؤولية. أما المبحث الثالث: فكان مخصصاً لبيان الحكم الشرعي في ضمان الطبيب فقهيا كما قررته بعض المذاهب الفقهية، سواء من العلماء القدماء أو من المعاصرين. وخلص البحث إلى مجموعة من النتائج تمثلت في: عدم مسؤولية الطبيب الحاذق حال قيامه بواجبه على أكمل وجه، وأن الخطأ الفاحش جزاؤه أروش وديات على العاقلة، ويتحمل الطبيب عند الإهمال الضمان من الديات والأروش من ماله، وأن على الطبيب مسؤولية في مهنته رعاية لحق الإنسان المكرم المحترم. وقد اختتم البحث بأهم التوصيات منها: الاهتمام بالكادر الطبي بمختلف التخصصات وإنشاء مراكز تدريب تابعة للمؤسسات الرسمية، وإنشاء جهات رقابية على المراكز والمؤسسات الصحية.
The medical error and its impact on the patient - a contemporary jurisprudential study" aims to demonstrate the urgent need for a jurisprudential statement in this aspect. The importance of the topic is obvious as it relates to people s lives, which are a necessity. The problem of the research has been identified in questions: Does the doctor, the surgeon, and the anesthetic bear, in our modern time, the medical error or not? The course of structural research was made up of three sections. The first section included the definition of medical error and its types. The second section: it included a statement of medical liability and the health facility, and the extent of this responsibility. The third section: It explained the ruling of Shari a on the doctor’s guarantee jurisprudentially, as determined by some jurisprudential doctrines either from the old scholars or from the contemporary. The research concluded with a set of results. The skilled doctor does not bear the responsibility when he/she performs his/her duty to the fullest. The outrageous mistake should be punished by paying the indemnities and blood money. In the event of negligence, the docor guarantees the indemnities and the blood money from his/her money. The doctor is responsible in his/her profession to take care of the right of the honored and respected human being. The research ended with the most important recommendations, including: giving attention to the medical staff in various specialties, establishing training centers belonging to official institutions, and establishing supervisory bodies over health centers and institutions.
Keywords: العلوم الطبية -- الأخطاء الطبية -- المسؤولية المهنية -- الشريعة الإسلامية